Legal Protection for Singers as Performers in the Indonesian Music Industry: A Case Study of the Copyright Dispute between Ari Bias and Agnez Mo - Ahsan Ridho Faturahman; Wahyuni, Ridha (Al-Risalah, 2025)
This study investigates the legal reasoning underlying Decision No. 92/Pdt.Sus-HKI/Hak Cipta/2024/PN Niaga Jkt.Pst, which held singer Agnez Mo liable for copyright infringement, and examines the legal remedies available to performers under Indonesian copyright law. The purpose of this research is to evaluate the appropriateness of the court's interpretation regarding the responsibilities of performers in commercial music use, especially in the context of royalty obligations. Employing a normative legal research method, this study utilizes a statute approach and a case approach, drawing from primary legal sources such as Law No. 28 of 2014 on Copyright and Government Regulation No. 56 of 2021, along with relevant judicial decisions and academic commentary. The findings reveal two key results: first, the court's ruling failed to adequately consider the legal position and neighboring rights of performers as protected under Indonesian copyright law; second, performers—such as Agnez Mo—retain access to legal remedies, including cassation and judicial review, to challenge such rulings. The originality of this study lies in its critical legal analysis of a high-profile case that exposes the misapplication of statutory provisions concerning copyright and related rights. The implications of this research are significant for the development of clearer regulatory frameworks and for strengthening legal protections for performers in Indonesia’s creative industries.